Risk assessment of water inrush in tunnel through water-rich fault based on AHP-Cloud model. Issue 1 (1st January 2020) - Peng, Yaxiong; Wu, Li; Zuo, Qingjun; Chen, Chunhui; Hao, Yong
Abstract: Water inrush is a serious geological disaster in tunnel. Due to the complexity of geological conditions, large-scale water inrush is prone to occur in tunnel through water-rich fault during construction. Based on the comprehensive analysis of influencing factors, 8 evaluation indexes and the corresponding grading criteria are put forward to assess the risk of water inrush, and the risk of water inrush is divided into 4 levels. Synthesizing the standardization process and the analytic hierarchy process (AHP), a novel Cloud model is established to assess the risk of tunnel water inrush. The model is applied to the Longjinxi Tunnel to assess the risk level of water inrush. It is proved that the assessment results of the tunnel through water-rich fault is consistent with the actual situation, which verifies the reliability of evaluation model.